laurajanebuckl
laurajanebuckl
17-09-2015
Mathematics
contestada
Divide (x^3+2x^2-x-2) by (x-1)
Respuesta :
Julik
Julik
17-09-2015
[tex] \frac{x^3+2x^2-x-2}{(x-1)} =x^2+3x+2 \\ \\ x^3+2x^2-x-2= \\= x^2(x+2)-(x+2) \\ =(x+2)(x^2-1)=(x+2)(x-1)(x+1) \\ \\ \frac{x^3+2x^2-x-2}{(x-1)} = \frac{(x+2)(x-1)(x+1)}{x-1} =(x+2)(x+1)=x^2+3x+2[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 11+ )
Otras preguntas
whats the answer to 1/2(4x-6)=11
PLEASE Haikus generally focus on city life. True False
What three components make up most magmas?
What is the greatest common factor of 48m5n and 81m2n2
What's the answer to this?
12 . American colonists felt they were subject to tyrannical King. As a result, which of the following elements did they put in the Declaration of Independence
Make a mapping diagram for the relation {(–2, –6), (0, 3), (1, –5), (5, 0)} I don't understand this.
What type of living arrangements do most university students live in for at least the first and second years of colleges
21 minus (minus 95)=
Which sentence correctly changes the underlined word to a direct object pronoun? Juanita quiere las flores. Question 6 options: Juanita quiere las. Juanita las
ACCESS MORE